Application of AI in the User Interface Design Process - Curyl, Piotr (Zastosowanie AI w procesie projektowania interfejsu użytkownika, 2024)
Aim: The objective of the article is to analyse the impact of artificial intelligence (AI) on the quality, efficiency and cost of user interface (UI) design through a systematic literature review. Notwithstanding the burgeoning interest in AI across diverse disciplines, there persists a dearth of systematised research addressing its tangible impact on UI design. The article aims to identify and analyse key aspects of this impact based on available academic publications and industry reports. Methodology: The study is based on a systematic literature review, including academic publications and industry reports from 2018-2024. The analysis considers the use of AI in UI design, process automation, impact on interface quality and usability, and implementation costs. Key sources include Google Scholar, ResearchGate, IEEE Xplore and Forrester and Gartner reports. It should be noted that the study is limited to the analysis of available literature in Polish and English, which is one of the limitations of the presented review. Results: The analysis of the literature indicates that AI contributes to the quality of user interfaces by reducing errors, analysing usage patterns and potentially automatically adapting UIs to user preferences. AI tools, such as generative design models, can speed up the UI development process and automate repetitive tasks. The results of the review also suggest that while AI has the potential to reduce design costs, it requires investment in tools and training of professionals, and its impact on costs is not clear at the current stage of technology development. Implications and recommendations: The results of the literature review suggest that the use of AI in UI design can increase design efficiency and potentially improve product quality. Companies should consider both the potential benefits and challenges of implementing AI, such as ethical issues and the need for ongoing competence development. Further empirical research into the actual impact of AI on designers’ creativity and long-term financial efficiency is recommended. Originality/value: The article provides a structured analysis of the use of AI in UI design based on a literature review, filling an existing research gap by synthesising current trends and potential future directions of AI technology in the context of user interfaces. The conclusions of the review may be of value to both researchers and practitioners in the UX/UI industry seeking up-to-date knowledge on the application of AI in the field.
Business Informatics = Informatyka Ekonomiczna, 2024, Nr 1-2 (67-68), s. 117-126
Keywords: artificial intelligence; user interface; UX/UI; automation; generative AI; sztuczna inteligencja; interfejs użytkownika; automatyzacja; generatywne AI